Approach to splitting a horseshoe kidney for deceased donor transplantation - Bruce Li; Jirong Lu; Patrick P. Luke (Urology Video Journal)
Background: The complex anatomy of horseshoe kidneys are associated with high discard rate and poor outcomes, particularly when split for transplantation. We described the surgical approach for en bloc procurement, splitting, and reconstruction of a horseshoe kidney from a deceased donor. Methods: A horseshoe kidney with multiple renal arteries and veins was procured bloc from a 27-year-old donor following neurologic brain death. Following en bloc procurement, back-table dissection facilitated vascular, collecting system reconstruction, splitting of the isthmus. The left renal moiety was transplanted into a 31-year-old female with two failed transplants, while the right moiety, with preserved isthmus, was transplanted into a 49-year-old male undergoing his first transplant. Results: Both grafts were transplanted successfully with immediate graft function after a cold ischemia time of 8 h 40 min (left), 13 h 49 min (right). Total surgery times were 3 h 29 min (left), 3 h 37 min (right). Post-operative course was unremarkable, besides one episode of acute pancreatitis managed conservatively for the recipient that received the left moiety. Nine-month follow-up showed excellent graft function in both recipients. Conclusion: Successful transplantation of a split horseshoe kidney requires careful anatomical assessment, precise dissection, and reconstructive techniques.